Hypocholesterolemic and immunostimulatory effects of orally applied Enterococcus faecium M-74 in man - Mikes, A; Ferencík, M; Jahnová, E; Ebringer, L; Ciznár, I (Folia microbiologica, 1995)
Lyophilized Enterococcus faecium M-74 was administered to 12 adult subjects in a daily oral dose of 5 x 10(9) bacteria for six weeks. The bacterium temporarily colonized the host intestine and its excretion with stool persisted for five weeks after the last does. The mean levels of serum cholesterol and LDL showed a a biphasic effect--an elevation followed by a sharp decrease (on day 64 of investigation). The decrease corresponded in time with a significant increase in the ability to reduce iodonitrotetrazolium and superoxide production by peripheral neutrophils incubated with zymosan or phorbol myristate acetate, and also with an elevated production of IgG by peripheral blood mononuclear cells. Hence, intake of E. faecium may have a hypocholesterolemic and immunostimulatory effect. It was also demonstrated that E. faecium significantly reduced the average activity of beta-D-glucuronidase in stools.
Keywords: Zymosan; dospělí; neutrofily; anticholesteremika; ženské pohlaví; lidé; imunoglobulin G; tetradekanoylforbolacetát; Antibody Formation; Enterococcus faecium; senioři; Lipoproteins, LDL; Oxidation-Reduction; adjuvancia imunologická; oxidace-redukce; Aged; lidé středního věku; respirační vzplanutí; Humans; lipoproteiny LDL; Tetradecanoylphorbol Acetate; aplikace orální; zymosan; Administration, Oral; Respiratory Burst; tvorba protilátek; mužské pohlaví; Neutrophils; Adult; Immunoglobulin G; Anticholesteremic Agents; Cholesterol; Male; Adjuvants, Immunologic; cholesterol; Freeze Drying; lyofilizace; Middle Aged; Female